Fatores de risco para hepatite B : um estudo caso-controle - Dias, Jerusa Araújo (2011)
Hepatitis B is still a major problem of health care in Brazil. This investigation aimed to describe the association between risk factors and the infection by the hepatitis B virus (HBV) in the subjects attending the primary health care facilities in the city of São Mateus, Espírito Santo State. A secondary objective was to identify vulnerable segments of the population. The study was designed as a case-control approach in which the cases were those Hepatitis B patients diagnosed by the Family Health Strategy facilities or by the Center of testing and advising for sexual transmitted diseases from December 2009 to July 2010 and the control group consisted of individuals with no markers of infection by the hepatitis B virus paired by gender, age and treatment location. Seventy four patients and 74 controls were interviewed through a questionnaire which approached the variables: race/color, marital status, occupation, place of residence in the city, health care facility used, educational background, family income, pregnancy or not, reason why a treatment was searched, triage in the blood bank, number and type of sexual partners, use of condoms, sexually transmitted diseases background, use of drugs and their type, dental treatment, tattoo and/or piercing presence. Data were submitted to a bivariate analysis using Chi-square test or Fisher Exact test to verify the presence of association between the candidate independent variables and the positive result to a immunologic marker of (HVB). Those variables with a p<0,20 for an association with the outcome were included in a multivariate analysis by the method of logistic regression, being previously tested for the occurrence of interactions with each other. The limit of significance adopted was 0.05. Continuous variables (income, age and time living in the Municipality) were compared by Mann-Whitney test. There was an association between the occurrence of infection by the hepatitis B virus and the residence in rural area (OR = 6.08; CI95%: 1.550-23.876; p<0,01), educational background – none (OR = 8.9; IC95%: 1.005-80.129; p<0,05) and high school (OR = 0.411; CI95%: 0.187-0.904; p<0,02). In conclusion, the study results suggest that apart from facing hepatitis B via vaccination and via the encouragement to use condoms in all sexual relations, further specific actions must be directed to the most vulnerable segments of the population like the least-favored ones from the educational point of view and the inhabitants of the rural areas.